2014
DOI: 10.1007/s10728-014-0280-9
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing Cultural Change in Care for Older People: Seeing the Cherry Tree Blossom

Abstract: There is a need for person-centred approaches and empowerment of staff within the residential care for older people; a movement called 'culture change'. There is however no single path for achieving culture change. With the aim of increasing understandings about cultural change processes and the promotion of cultural values and norms associated with person-centred practices, this article presents an action research project set on a unit in the Netherlands providing care for older people with dementia. The proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Later on in the process they performed a number of actions to maintain the implementation of VCM, such as developing and financing a long-term implementation plan and including VCM in the regular business processes. This process is consistent with Snoeren et al (2014), who concluded that improvement of care and cultural change in nursing homes are dynamic, interactive and non-linear processes that take place at the same time. These are complex processes, making prediction and control difficult, and they require managers with a supportive and flexible attitude.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Later on in the process they performed a number of actions to maintain the implementation of VCM, such as developing and financing a long-term implementation plan and including VCM in the regular business processes. This process is consistent with Snoeren et al (2014), who concluded that improvement of care and cultural change in nursing homes are dynamic, interactive and non-linear processes that take place at the same time. These are complex processes, making prediction and control difficult, and they require managers with a supportive and flexible attitude.…”
Section: Discussionsupporting
confidence: 89%
“…On wards where compliance with VCM was higher, the training helped caregivers to reflect, correct and encourage each other. Providing feedback appears to be as important as the intervention itself, because it stimulates 'ongoing learning' (Eggenberger et al 2013, Snoeren 2015. As reported before, the long duration of the training, the followup sessions and coaching-on-the-job are also important 'boosters' to successful implementation of VCM (Lawrence et al 2012, Boersma et al 2015.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations